Forest Dynamics and the Analysis of a Reaction-Diffusion Forest Model - Tasnim, Farah; Alam, Md Shah; Kamrujjaman, Md (GANIT: Journal of Bangladesh Mathematical Society, 2023)
In this research, we study the dynamics of ecological models governed by differential equations. Ecology provides insight into the interaction between forest organisms, and interrelated processes regarding flora, fauna, and numerous other species. In particular, the results support population thresholds necessary for survival in some instances. Subsequently, we explore the response of mangroves of different regions to natural calamities and man-made disasters. A reaction-diffusion model has been developed to see the dynamics of the tidal woods and wetlands. Sundarbans, the largest mangrove of Bangladesh, are victim to a vast amount of hazardous events. This mathematical study of mangroves is unprecedented in such a manner. Furthermore, we continue the study of a forest ecosystem governed by an age-structured parabolic-ordinary system. We study some properties of an abstract parabolic equation, the dynamical system, and the limit sets. The model demonstrates a Lyapunov function which denotes some vital properties of the limit sets. GANIT J. Bangladesh Math. Soc. 43.1 (2023) 26- 36